Optimization of response and sufficiency index in Bt cotton (Gossypium spp.) through optical sensor based nitrogen management - ASHWINI, T R; POTDAR, M P; KUMAR, B N ARAVIND; PATIL, P L; NIRMALNATH, P JONES (The Indian Journal of Agricultural Sciences, 2022)
To break the productivity barriers in Bt cotton (Gossypium spp.), adoption of optical sensor based nitrogen (N) management practices is the need of the hour. In light of this, a field experiment was conducted at the main Agricultural Research Station, Dharwad, Karnataka during rainy (kharif) season 2019 and 2020 to optimize the response index (RI) and sufficiency index (SI) for real time nitrogen management in Bt cotton through optical sensors. Experiment was conducted in split plot design with 16 treatment combinations having 2 genotypes (main plot) and 8 N management practices (subplot). Pooled data indicated that non-significant (P=0.3480) difference in seed cotton yield was observed with genotypes (First Class and Ajeet 155 recorded 3313 and 3159 kg/ha, respectively). Seed cotton yields varied significantly (P.9999). Similarly, N supplementation at 1.1–1.5 RI and 81–90% SI recorded significantly (P